2007
DOI: 10.1016/j.jcrs.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Asphericity of the anterior human cornea with different corneal diameters

Abstract: There were differences in sagittal corneal height calculations considering constant or variable models of Q. Concern arises when surgical interventions depend on corneal Q-values to predict the outcomes. Surgeons should be aware which procedure is behind Q computing by different corneal topographers and that a constant Q-value cannot reflect the actual shape of the cornea as significant departures from the actual sagittal height can arise depending on which Q-value is assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
10
21
1
Order By: Relevance
“…It should be considered that the geometry of the anterior corneal surface of the human cornea can be adjusted to a conical section that is characterized by an asphericity (Q) and a specific value for the radius of the apical curvature (r 0 ). 41,42 The Q characterizes the gradual curvature change in the corneal surface from center to periphery. [42][43][44] The most commonly accepted value for Q in young adult patients is À0.23 G 0.08 (prolate ellipsoid).…”
Section: Corneal Asphericitymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be considered that the geometry of the anterior corneal surface of the human cornea can be adjusted to a conical section that is characterized by an asphericity (Q) and a specific value for the radius of the apical curvature (r 0 ). 41,42 The Q characterizes the gradual curvature change in the corneal surface from center to periphery. [42][43][44] The most commonly accepted value for Q in young adult patients is À0.23 G 0.08 (prolate ellipsoid).…”
Section: Corneal Asphericitymentioning
confidence: 99%
“…[42][43][44] The most commonly accepted value for Q in young adult patients is À0.23 G 0.08 (prolate ellipsoid). 41,45 Positive values of Q would denote the presence of an oblate surface (ie, corneas after myopic ablation with the excimer laser or orthokeratology treatments), and a null value (Q Z 0) would represent a completely spherical surface. In an ectatic cornea (Figure 2), the anterior protrusion generates an increase of the corneal prolatism with an associated negativization of Q (Table 1).…”
Section: Corneal Asphericitymentioning
confidence: 99%
“…In addition, Q-values were calculated for different corneal diameters (3.0 mm, 4.0 mm, 5.00 mm. 6.00 mm, 7.00 mm and 8.00 mm) using the calculation procedures implemented in the Vol-CT 6.89 package (Sarver & Associates Inc.) for a 7 mm pupil size, following the recommendations of González et al [18].…”
Section: Refractive Error Corneal Topography and Q Calculationsmentioning
confidence: 99%
“…This idea is consistent with the results of an earlier study by Patel et al [17], in which it was found that the conic section is a poor estimate of the corneal periphery, and the authors suggested the use of different conic sections with different shape factors depending on the region to be represented. Recently, Gonzalez-Méijome et al [18] reported that the rate of change in corneal Q with different corneal diameters increases as corneal astigmatism increases. However, no previous study has been designed to explore the relationship between Q and corneal power for different diameters.…”
Section: Introductionmentioning
confidence: 99%
“…The explanation for these results is straightforward. Before refractive surgery, the corneal anterior surface is prolate [12], which means the lowest of the radius of curvature is at the apex of the cornea. However, after refractive surgery, the corneal anterior surface is oblate [13,14], meaning that the highest radius of curvature is at the apex of the cornea.…”
Section: Discussionmentioning
confidence: 99%